Socialization of Utilization of Coastal Boundary Space and Coastal Abrasion in South Galesong District - K, Riswal.; Maricar, Farouk; Thaha, Muh Arsyad; Lopa, Rita Tahir; Mustari, A. Subhan; Bakri, Bambang; Pongmanda, Silman; Pallu, Muh. Saleh; Hatta, Mukhsan Putra; Puspita, A. Ildha Dwi (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
South Galesong District, South Sulawesi, is a coastal area facing a serious threat due to beach erosion, exacerbated by the improper use of coastal setback areas that do not align with their ecological functions. The South Galesong District Government and the community of Mangindara Village, as partners in this program, face challenges in sustainably managing coastal setback areas. This community service program aims to raise public awareness and understanding of coastal setback management and erosion mitigation through various educational methods and community-based training. The implemented methods include lectures, distribution of educational leaflets and banners, as well as pre-test and post-test assessments to measure the improvement in public understanding. Additionally, community-based mitigation training was conducted using a hybrid approach that combines nature-based solutions and engineering techniques for erosion control. Baseline evaluation through questionnaires indicated that the initial level of public understanding regarding coastal setbacks and erosion issues ranged between 27% and 37.5%. After the program, post-test results showed a 40% increase in understanding of coastal protection structure planning, with an overall average improvement of 35.66%. Based on the results of this community service program, it can be concluded that the socialization of coastal setback utilization and beach erosion has had a significantly positive impact on public understanding in South Galesong District. The educational materials proved effective in increasing awareness of the importance of coastal setbacks, the risks of erosion, and the planning of protective coastal structures. Moving forward, it is expected that fishermen and communities residing in coastal setback areas will have an even greater awareness of the importance of sustainable coastal setback utilization in accordance with ecological functions, as well as a better understanding of coastal erosion.